Formulation and application of nanosilver-infused cream in prevention and treatment of mastitis in dairy cows - Chau, Nguyen Hoai; Hien, Dao Trong; Thuy, Nguyen Thi; Ha, Doan Quang; Duong, Dang Thi; Loan, Tran Thi; Linh, Phung Thi Dieu; Luu, Tang Xuan; Tan, Ngo Dinh; Tua, Tran Van (Academia Journal of Biology, 2019)
Research on formulation of nanosilver-infused cream was carried out at the Institute of Environmental Technology and the effects of this cream in prevention and treatment of mastitis in dairy cows were assessed at Bavi Cattle and Forage Research Center. Cream with 0.4% carbomer was infused with silver nanoparticles for high uniformity and long-term stability. At concentrations of 50–250 ppm, nanosilver-infused cream proved to be effective against mastitis pathogens such as Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa. Nanosilver cream at concentrations of 150 ppm had the best effect on clinical and subclinical mastitis prevention in dairy cows. Combining nanosilver cream with ceftiofer antibiotic achieved excellent treatment rate, up to 93.33%. For prevention of dairy mastitis, silver cream can be used at a concentration of 150 ppm 15 days before calving and for the whole milking period. Using nanosilver cream in combination with antibiotics led to highly effective mastitis treatment.